Analogue‐to‐information conversion using multi‐comparator‐based integrate‐and‐fire sampler. Issue 3 (1st February 2015) - Wen, Fangqing; Tao, Yu; Zhang, Gong
Abstract : A new methodology for sparse signal acquisition using a multi‐comparator‐based integrate‐and‐fire sampler is presented. By employing the randomness of comparator voltages, the original analogue signal is converted into a series of binaries and is guaranteed to be precisely recovered from these measurements. The proposed scheme operates with a sub‐Nyquist rate, which requires neither a high‐speed linear feedback shift register nor an accurate analogue‐to‐digital converter. The experimental results demonstrate the effectiveness of the proposed scheme.